BATTER PILES UNDER INCLINED COMPRESSIVE LOADS - Yousif J. Al-Shakarchi; Mohammed Yousif Fattah; Ihsan K. Kashat (Journal of Engineering, 2003)
The behaviour of batter piles under inclined compressive loads is of considerable importance,yet, not enough information is available in literature on the subject. The tests canied out in this paper were performed on a single inclined pile under various load inclinations in sand. The results indicate that the highest ultimate compressive load for vertical pile occurs at (30) load inclination. At small load inclinations, a positive batter pile has greater ultimate compressive load than that of a negative batter pile. The trend changes at higher Ioad inclinations. The slip surface analysis is recognised to be too complicated to have a definite solution.